Mengenali warga tua desa di Malaysia: Profil sosial dan pengaturan tempat kediaman - Wan Ahmad, Wan Ibrahim (College of Law, Government and International Studies, Universiti Utara Malaysia, 2010)
Worldwide, the elderly populations are increasing very rapidly.In Malaysia, as the size of the elderly population grows, it is more evident that the process of urbanization has become part of the rural lives.The changing family structure of the rural folks has led to many elderly populations in rural areas to be living alone without care and support from their children.The objective of this article is to explore the social and demographic profile, and living arrangement patterns of the elderly populations in the rural areas.To achieve this objective, 214 elderly respondents of 60 years and above in rural Kelantan were selected.Results show that most of the respondents are among the economically-deprived groups in the community.Most of the respondents were dependent on traditional agriculture activities for their livelihood. Urbanization that has taken place in the mukims neighbouring the town centre provided new employment oppurtunities to the elderlies. Many of them are involved in small businesses and as wage-labors. In addition, more elderly populations are living on their own. On the whole, the elderly populations still receive sufficient care and support from their children and they are satisfied with the support.